Impact of internal audit competence and objectivity on quality audit results - Atang Hermawan; Agus Bustomi (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
Experience in conducting audits carefully, accurately, and objectively is the main competency that must be possessed by auditors. In fact, what is happening in the field shows that there are still irregularities and errors related to the audit process. This is the basis of research in revealing the effect of competence and objectivity on audit quality. The research was conducted using a survey method conducted at PT. Pindad Bandung. The data obtained were analyzed quantitatively with multiple linear regression analysis techniques, hypothesis testing t, and F test to test simultaneously. The results show that there is an influence of competence and objectivity of internal audit on audit quality at PT Pindad Bandung which is indicated by the calculation results of 75%. With the results of this study, it is hoped that it can be used as a reference for every company to always improve the competence of each auditor.